PERSEPSI PETANI TERHADAP PERFORMANSI KERJA PENYULUH PERTANIAN LAPANGAN DALAM PENGEMBANGAN AGRIBISNIS KEDELAI DI KECAMATAN TOROH KABUPATEN GROBOGAN - Listya Puspitasari (Universitas Wahid Hasyim, 2009)
This research aimed to study farmer's perception on PPL performance in soya beans agribusiness. There were three indicators use to evaluate PPL performance; first, responsivity; second, responsibility; and third, services quality. Primary data were obtained by direct interview use a questionnaire. Data were analyzed by non parametric and descriptive analysis. The result indicated that responsivity PPL with farmer's need could be classified as mediocre with score of 291 or 57,06% of maximum score. The score of PPL responsibility was 352 or 69,2% of maximum score and categorized as good level and services quality score were 2105 or 51,59% of maximum score. Key words : PPL performance, farmer's perception